Borrowing Agreement with National Bank of Belgium. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
In light of the multilateral effort to ensure the adequacy of the financial resources available to the International Monetary Fund, and with a view to supporting the Fund's ability to provide timely and effective balance of payments assistance to its members, the National Bank of Belgium agrees to lend to the Fund an SDR denominated amount up to the equivalent of EUR 4.74 billion, on the terms and conditions set out in this policy paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Amount; Fund; Maturity Date; PP; SDR; Belgium